Analisis Pengembangan Pariwisata Berbasis GIS untuk informasi wisata di daerah Mukomuko - Aurora, Keisha; Sularno (Journal Of Informatics And Busisnes, 2024)
Mukomuko is a district located in Bengkulu Province, Indonesia. This region is known for its stunning natural beauty, including mountains, plantations and rivers flowing through fertile land. Mukomuko is also known as a fertile agricultural area with agricultural products such as coffee, coconut and rubber. Apart from its natural riches, Mukomuko has cultural diversity which is reflected in local traditions, customs and art. The friendly and warm people create a homely and welcoming atmosphere for visitors. With its abundant natural and cultural potential, Mukomuko is an attractive tourism destination. Tourists can enjoy its natural beauty, explore the mountainous area, and experience the unique life of the local community. As part of Bengkulu Province, Mukomuko contributes to the richness and diversity of Indonesian culture.